All You Wanted to Know About Mathematics but Were Afraid to Ask : Mathematics for Science Students - Lyons, Louis
Contenido volumen 2: Integrales; Operadores vectoriales; Ecuaciones diferenciales parciales; Series de Fourier; Modelos normales; Ondas; Matrices; Vectores propios y autovalores.